Training High School Students' Science Process Skills Through Phet Media in the Inquiry Model on Elasticity Material - Sopacua, Fryan; Sopacua, Venty (Journal of Science and Science Education, 2024)
This study aims to train the science process skills of high school students through phet media in an inquiry setting on elasticity material. The sample of this study was 27 students of class XI MIA-3. This study uses quantitative and qualitative descriptive research types. The trial design uses one group pretest–posttest design. The instrument in this study is the Test Instrument, in this case to measure the increase in students' science process skills before and after treatment using the inquiry model and phet media. Data analysis in this study was carried out using quantitative descriptive analysis. The data analysis technique used is qualitative descriptive analysis including: the results of the science process skills test. The results showed an increase in science process skills with an average Ngain of 0.80 with a high category and the achievement of an increase in each science process skill indicator above 70%, so it can be concluded that the inquiry model and phet media can train the science process skills of SMA A class XI MIA-3 students on elasticity material